2019
DOI: 10.1002/pat.4722
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bio‐based internal and external cross‐linkers based on tannic acid for preparation of antibacterial superabsorbents

Abstract: Recent researches focus on the synthesis of new cross‐linkers from natural resources. In the current work, functionalized tannic acid was employed as a replacement of petroleum‐based cross‐linkers because of its outstanding biochemical properties. Alkene‐ and epoxy‐functionalized tannic acids were synthesized as internal and external cross‐linkers, respectively. Cross‐linker structures were characterized with Ft‐IR and 1HNMR analysis. Different amounts, as well as different numbers of alkene functional group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 52 publications
(146 reference statements)
1
25
0
Order By: Relevance
“…Tannic acid (TA; Figure 1 ) is a natural tannin from the phenolic acid group and consists of a central glucose unit and ten gallic acid molecules attached to it [ 22 ]. It may be isolated from both herbaceous and woody types of plants [ 23 ]. TA is one of the main examples of tannins which can be efficiently extracted from natural sources with high efficiency, and thus, it attracts much scientific interest.…”
Section: Tannic Acidmentioning
confidence: 99%
See 3 more Smart Citations
“…Tannic acid (TA; Figure 1 ) is a natural tannin from the phenolic acid group and consists of a central glucose unit and ten gallic acid molecules attached to it [ 22 ]. It may be isolated from both herbaceous and woody types of plants [ 23 ]. TA is one of the main examples of tannins which can be efficiently extracted from natural sources with high efficiency, and thus, it attracts much scientific interest.…”
Section: Tannic Acidmentioning
confidence: 99%
“…Dabbaghi et al [ 23 ] have reported the tannic acid activity against Staphylococcus aureus and Escherichia coli which dependend on the phenolic hydroxyl groups content. Tannic acid was used as a polymer cross-linker, and final hydrogels showed antibacterial activity against both types of bacteria in the case of which the increased activity was related to increasing content of TA in the material.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The rheological properties were measured at 25 °C after placing the expanded gel particles on a parallel plate of a rheometer. The storage modulus (G′) and loss modulus (G″) were recorded at constant shear strain (0.2%) and a frequency ranging from 0.1–100 Hz [ 39 ].…”
Section: Methodsmentioning
confidence: 99%